PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI SEKOLAH TERHADAP MOTIVASI KERJA GURU DI MTSS AL-WASHLIYAH TEMBUNG - Abdillah, Abdillah; Yunus, Muhammad (Universitas Nurul Jadid, 2020)
This research was carried out to reveal 1) Is there an influence of the principal's leadership on teacher work motivation? 2) Is there an influence of school organizational culture on teacher work motivation? 3) Is there an influence of the principal's leadership on the culture of the school organization? 4) Is there an influence on the principal's leadership on the teacher's work motivation through the culture of the school organization ?. This research was conducted using a quantitative approach to path analysis with a total sample of 30 people consisting of school principals and teachers. Data was collected using a Likert scale model questionnaire. Data were analyzed using simple and multiple correlation and regression techniques. The results revealed that the four issues raised proved to be very influential and significant. This proves that work motivation is determined by leadership. Work motivation is also determined by organizational culture, organizational culture is determined by leadership.